Recovery after an Ironman triathlon: sustained inflammatory responses and muscular stress - Neubauer, O.; König, D.; Wagner, K. H. (European Journal of Applied Physiology, 2008)
Ultra-endurance exercise, such as an Ironman triathlon, induces muscle damage and a systemic inflammatory response. As the resolution of recovery in these parameters is poorly documented, we investigated indices of muscle damage and systemic inflammation in response to an Ironman triathlon and monitored these parameters 19 days into recovery. Blood was sampled from 42 well-trained male triathletes 2 days before, immediately after, and 1, 5 and 19 days after an Ironman triathlon. Blood samples were analyzed for hematological profile, and plasma values of myeloperoxidase (MPO), polymorphonuclear (PMN) elastase, cortisol, testosterone, creatine kinase (CK) activity, myoglobin, interleukin (IL)-6, IL-10 and high-sensitive C-reactive protein (hs-CRP). Immediately post-race there were significant (P < 0.001) increases in total leukocyte counts, MPO, PMN elastase, cortisol, CK activity, myoglobin, IL-6, IL-10 and hs-CRP, while testosterone significantly (P < 0.001) decreased compared to prerace. With the exception of cortisol, which decreased below prerace values (P < 0.001), these alterations persisted 1 day post-race (P < 0.001; P < 0.01 for IL-10). Five days post-race CK activity, myoglobin, IL-6 and hs-CRP had decreased, but were still significantly (P < 0.001) elevated. Nineteen days post-race most parameters had returned to prerace values, except for MPO and PMN elastase, which had both significantly (P < 0.001) decreased below prerace concentrations, and myoglobin and hs-CRP, which were slightly, but significantly higher than prerace. Furthermore, significant relationships between leukocyte dynamics, cortisol, markers of muscle damage, cytokines and hs-CRP after the Ironman triathlon were noted. This study indicates that the pronounced initial systemic inflammatory response induced by an Ironman triathlon declines rapidly. However, a low-grade systemic inflammation persisted until at least 5 days post-race, possibly reflecting incomplete muscle recovery.